2004
DOI: 10.1073/pnas.0308280101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for the bidirectional modulation of synaptic plasticity in the prefrontal cortex by D1 receptors

Abstract: To address the role of D1 receptors in the medial prefrontal cortex, we combined pharmacological and genetic manipulations to examine long-term synaptic potentiation (LTP)͞long-term synaptic depression (LTD) in brain slices of rats and mice. We found that the D1 antagonist SCH23390 selectively blocked the maintenance but not the induction of LTP in the prefrontal cortex. Conversely, activation of D1 receptors facilitated the maintenance of LTP, and this effect is impaired in heterozygous D1 receptor knockout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
171
1
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(189 citation statements)
references
References 26 publications
13
171
1
4
Order By: Relevance
“…This finding is consistent with the idea that learning of strategies required to solve complex problems, such as the DNMTP task with retroactive interference, may have a long-lasting memory component that shares the cellular and molecular properties of other well studied long-term memory processes, i.e., gene expression and protein synthesis (4,31,32). In a recent paper, Huang et al (33) reported that long-term potentiation (LTP) can occur in the rat mPFC by applying repeated tetanizations to slice preparations and that this LTP is blocked by ANI. Our data further demonstrate that consolidation of learning strategies in the DNMTP task with retroactive interference requires protein synthesis and that the mPFC is a critical site for this learning-induced de novo proteins.…”
Section: Discussionsupporting
confidence: 86%
“…This finding is consistent with the idea that learning of strategies required to solve complex problems, such as the DNMTP task with retroactive interference, may have a long-lasting memory component that shares the cellular and molecular properties of other well studied long-term memory processes, i.e., gene expression and protein synthesis (4,31,32). In a recent paper, Huang et al (33) reported that long-term potentiation (LTP) can occur in the rat mPFC by applying repeated tetanizations to slice preparations and that this LTP is blocked by ANI. Our data further demonstrate that consolidation of learning strategies in the DNMTP task with retroactive interference requires protein synthesis and that the mPFC is a critical site for this learning-induced de novo proteins.…”
Section: Discussionsupporting
confidence: 86%
“…In five neurons tested, the input resistance (R in ) of IL neurons from vehiclepretreated rats was 298.9 ‫ע‬ 23.7 M⍀ (n = 5), which was not different from that of vehicle-pretreated rats (295.0 ‫ע‬ 18.2 M⍀, n = 5, P > 0.1). Orthodromic stimuli applied to the layer II of rat prefrontal cortex slices elicited excitatory postsynaptic currents (EPSCs) in layer V (Huang et al 2004). Bath application of the AMPA receptor antagonist CNQX (10 µM) plus the NMDA receptor antagonist D-APV (50 µM) blocked the EPSCs, revealing an IPSC that was completely blocked by bicuculline (10 µM), confirming the mediation by GABA A receptors (Fig.…”
Section: Tolerance To Win-induced Inhibition Of Gabaergic Neurotransmmentioning
confidence: 69%
“…In addition, activation of D1-class receptors lowered the threshold for both LTP and LTD at CA1 synapses in vivo [62]. Similarly, in deep layer PFC synapses and hippocampal-PFC synapses, agonists of D1-class receptors facilitated, whereas antagonists impaired, NMDAR-dependent LTP via cAMP-dependent mechanisms [63][64]. Acting at both D1-and D2-class receptors, DA at high concentrations facilitates LTD, whereas at low concentrations promotes LTP [65].…”
Section: Functional Evidencementioning
confidence: 99%
“…In the nucleus accumbens, most studies report that DA attenuates corticoaccumbal glutamatergic input by acting on D1-class receptors [6]. This attenuation, according to one proposed mechanism, is mediated by an inhibitory feedback action of adenosine, liberated following facilitation of NMDARs by D1-mediated PKC activation in postsynaptic neurons [58] layer PFC synapses and hippocampal-PFC synapses, agonists of D1-class receptors facilitated, whereas antagonists impaired, NMDAR-dependent LTP via cAMP-dependent mechanisms [63][64]. Acting at both D1-and D2-class receptors, DA at high concentrations facilitates LTD, whereas at low concentrations promotes LTP [65].…”
Section: Functional Evidencementioning
confidence: 99%